PROKRASTINASI AKADEMIK MAHASISWA PADA MATA KULIAH ALJABAR LINEAR - Cahyadi, Rahman (JURNAL e-DuMath, 2018)
ABSTRACT Each lecturer gives a college contract at the beginning of the lecture meeting, one of the contents is about the timetable for collecting tasks. It  found  that there are students whose job values are low because they often delay the collection of tasks. Because delays in the collection of tasks have an effect on the low value of student assignments, then it needs to be analyzed more about the factors causing delay of academic duty of student. This study only consists of one variable and its descriptive nature taken without formulation of hypothesis. Population in this research is all student of mathematics education force 2014 and 2015 STKIP Muhammadiyah Pringsewu Lampung which amounts to 66. The sample of the research is the students who are indicated to have delayed academic task. The sampling technique used is purposive sampling technique. Based on the results of the study can be concluded that the factors causing academic procrastination internal factors include students attitudes toward learning, factors of learning concentration, and study habits while the external factors include the factors of facilities and infrastructure. Internal factors are more dominant as factors of academic procrastination, this means that the cause of academic procrastination or postponing behavior comes from within the student. Keyword : Academic procrastination, factors of academic procrastination.